EXTH-46. MRS BASED BIOMARKERS OF IDH1 MUTANT GLIOMA RESPONSE TO THE IDH INHIBITOR BAY-1436032. (12th November 2021) - Hong, Donghyun; Minami, Noriaki; Taglang, Céline; Batsios, Georgios; Gillespie, Anne Marie; Pieper, Russell; Costello, Joseph; Viswanath, Pavithra; Ronen, Sabrina
Abstract: Gliomas are the most prevalent type of brain tumor in the central nervous system. Mutations in the cytosolic enzyme isocitrate dehydrogenase 1 (IDH1) are a common feature of primary low-grade gliomas, catalyzing the conversion of α-ketoglutarate (αKG) to the oncometabolite 2-hydroxyglutarate (2HG), and mutant IDH1 is a therapeutic target for these tumors. Several mutant IDH inhibitors are currently in clinical trials, nonetheless, complementary non-invasive early biomarkers to assess drug delivery and potential therapeutic response are still needed. The goal of this study was therefore to determine the potential of 1 H and hyperpolarized 13 C magnetic resonance spectroscopy (MRS)-based biomarkers as indicators of mutant IDH1 low-grade glioma response to treatment with the clinically-relevant IDH1 inhibitor BAY-1436032 in cells and animal models. Immortalized human astrocytes engineered to express mutant IDH1 were treated with 500nM (IC50 value) of BAY-1436032 and BT257 tumors implanted in rats were treated with 150mg/kg of BAY-1436032. To assess steady-state metabolite levels, 1 H MRS spectra were acquired on a 500 MHz MRS cancer for cells and a 3 T scanner for animal studies. To assess metabolic fluxes, we used hyperpolarized 13 C MRS and probed the fate of hyperpolarized [1- 13 C]αKG. 1 H MRS showed a significant decrease in 2HG as well as a significant increase in glutamate (Glu) and phosphocholine (PCh) following BAY-1436032 treatment in both cell and animal models compared to controls. Furthermore, hyperpolarized 13 C MRS showed that hyperpolarized 2HG production from hyperpolarized [1- 13 C]αKG was decreased and hyperpolarized glutamate production from hyperpolarized [1- 13 C]αKG was increased in the BAY-1436032 treated groups compared to controls. These findings are consistent with our previous study, which investigated the MRS-detectable consequences of two other mutant IDH inhibitors: AG120 and AG881. Collectively, our work identifies translatable MRS-based metabolic biomarkers of mutant IDH1 inhibition.